Automatic Steering System on The Prototype Electric Car UMSIDA - Indah Sulistiyowati; Miftachur Rifki Antoni (Fakultas Teknik Universitas Bhayangkara, 2016)
Currently the electronic device can not be separated from human life, especially is the gadget. Gadgets in daily activities is almost inseparable from our grasp, from children to adults. Many devices are now directly connected with android smartphone. Hence the idea to do some research occurred android smartphone is connected to a steering system of the car. In this case study is used as a prototype electric car UMSIDA. Here we create an electronic circuit that we put on the car steering system, which by using blutooth connection connects to an android smartphone that we use. As for the electronic devices we use Arduino is programmed using C language to run the motor that moves according to the input data transmitted via android smartphone. Where the results of tests show that the speed turns on bluetooth pairing process is more influenced by the android version and hardware high.